An Analysis of the Dual Opposition Structure of Life and Death Presented in Ancient Myths - Wang Xiao Yu (International Journal on Integrated Education, 2022)
Binary opposition is the central idea of structuralist criticism. Based on the theory of structuralist mythology, this paper uses the comparative method to analyze the binary opposition structure model of life and death by taking the typical myths of ancient Greece and ancient China as cases. Explores the ancient times the deep psychological structure of the ancestors, feel the deep reasons for the formation of different national cultures and psychology. Purpose attaches importance to the value of human life, inherit and carry forward the excellent national spirit.